A MODIFIED ON TWOFISH ALGORITHM BASED ON CYCLIC GROUP AND IRREDUCIBLE POLYNOMIAL IN GF (28) - muhajer, suhad; S. Rahma, Dr. Abdul Monem (Al-Qadisiyah Journal of Pure Science, 2020)
In this “article”, a “new “adjustment” is made on Two-fishalgorithm based on using a new operation called cyclic group extended # (CGE#) operation for increasing the randomness of algorithm. This isa new operation works on 8-bits and using 30 tables constructed with cyclic group and multiplication in Galois Field (GF) (28). A new (CGE#) operation is used instead of (X-OR)“operation in “each “round of Fe-istel of Two-fish. This is done by using dual keys: one key is used for selecting one table among 30 tables, and the other” key” is used for: encryption: and “decryption. The proposed algorithms are evaluated by using many security metrics such as complexity, NIST, histogram and correlation coefficients. The modification has givengood results in these metrics, and this leads to make the proposed algorithmmuch more robust against many the attacks.